Between Israel and Phoenicia: The Iron IIA–B Fortified Purple-dye Production Centre at Tel Shiqmona - Shalvi, Golan (Tel Aviv, 2023)
The history of Tel Shiqmona, on Israel’s Carmel coast, in the Iron Age has remained almost totally obscure since its excavation some 50 years ago. Recent analysis has revealed the site’s singularity—the only one around the Mediterranean that can be demonstrated to have produced the luxurious purple dye for half a millennium. This article is the first discussion of a central episode (three strata) in the site’s history. We argue that during the Late Iron IIA, the Kingdom of Israel, probably under the Omrides, replaced a small Phoenician village with a fortified casemate enclosure in order to control and institutionalise the production of the dye and other industries. These peaked under Jeroboam II, and subsequently the fort was ravaged during the period of unrest in Israel after this monarch’s reign. We discuss the historical and cultural picture emerging from a meticulous analysis of the stratigraphy and finds and address trade contacts and regional, historical and geopolitical contexts.